Can Methods Do Good? Ethnology and Multi-species Research as a Response to Covid-19 - Tallberg, Linda; Huopalainen, Astrid; Hamilton, Lindsay (Ethnologia Fennica, 2020)
In this conversational essay, three scholars working in the field of human—animal studies discuss the multi—species work that is underway in ethnology. Examples of different methodological approaches are highlighted; multispecies ethnography, crystallization, feminist dog-writing and écriture feminine. By reflecting on the value of such techniques, the authors contend that a renewed enthusiasm for methodological innovation can pave the way for more rounded accounts of social life, bringing animals and their agencies into clearer focus as companions, workers and beings in their own right. This is regarded as both an intellectual and ethical pursuit, with methods placed at the heart of the endeavour.